Islamic History as a Global Network: A Network Analysis Approach in Contemporary Islamic Historiography - Ibrahim Badhusha Parakkallil; Hafiz Aamir Ali; Muhammet Aslanoğlu; Serkan Rasit Kivrak; Keziban Mursel Cakir (Yayasan Albahriah Jamiah Indonesia, 2026)
Islamic historiography is generally structured through territorial, dynastic, and chronological frameworks, resulting in a fragmented understanding of the cross-regional relations that shaped the development of the Islamic world. This tendency leaves gaps in our understanding of the relationships among intellectual centers, economic networks, and social mobility on a transregional scale. This article aims to analyze patterns of global connectivity in Islamic history using a network analysis approach to reconstruct relationships among scholars, scientific institutions, trade routes, and Muslim communities across regions. This research uses a qualitative-historical method based on library studies, analyzing Islamic historiographic literature, historical sources, biographies of scholars, travelogues, and trade studies in Eurasia and the Indian Ocean. A network analysis framework is used to map the nodes, relationships, and connectivity flows that shape the historical structure of the Islamic world. The results of the study reveal a layered network pattern connecting centers of knowledge in the Middle East, South Asia, Southeast Asia, and Africa through scholarly travel, scholarly transmission chains, and intellectual correspondence. The scholarly network serves as a mechanism for knowledge transmission, fostering epistemic integration across regions. At the same time, trade networks formed corridors of economic, cultural, and religious interaction that accelerated the circulation of ideas, commodities, and Muslim identities. The mobility of migrants, diasporas, and students strengthened the position of various cities as strategic nodes in the global Islamic network. These findings affirm Islamic history as a relational system shaped by transregional connectivity and enrich contemporary Islamic historiography with a more integrative, global-network perspective.